Systemic Bevacizumab for Treatment of Respiratory Papillomatosis: International Consensus Statement. (6th January 2021) - Sidell, Douglas R.; Balakrishnan, Karthik; Best, Simon R.; Zur, Karen; Buckingham, Julia; De Alarcon, Alessandro; Baroody, Fuad M.; Bock, Jonathan M.; Boss, Emily F.; Bower, Charles M.; Campisi, Paolo; Chen, Sharon F.; et al.
Abstract : Objectives/Hypothesis: The purpose of this study is to develop consensus on key points that would support the use of systemic bevacizumab for the treatment of recurrent respiratory papillomatosis (RRP), and to provide preliminary guidance surrounding the use of this treatment modality. Study Design: Delphi method‐based survey series. Methods: A multidisciplinary, multi‐institutional panel of physicians with experience using systemic bevacizumab for the treatment of RRP was established. The Delphi method was used to identify and obtain consensus on characteristics associated with systemic bevacizumab use across five domains: 1) patient characteristics; 2) disease characteristics; 3) treating center characteristics; 4) prior treatment characteristics; and 5) prior work‐up. Results: The international panel was composed of 70 experts from 12 countries, representing pediatric and adult otolaryngology, hematology/oncology, infectious diseases, pediatric surgery, family medicine, and epidemiology. A total of 189 items were identified, of which consensus was achieved on Patient Characteristics (9), Disease Characteristics (10), Treatment Center Characteristics (22), and Prior Workup Characteristics (18). Conclusion: This consensus statement provides a useful starting point for clinicians and centers hoping to offer systemic bevacizumab for RRP and may serve as a framework to assess the components of practices and centers currently using this therapy. We hope to provide a strategy to offer the treatment and also to provide a springboard for bevacizumab's use in combination with other RRP treatment protocols. Standardized delivery systems may facilitate research efforts and provide dosing regimens to help shape best‐practice applications of systemic bevacizumab for patients with early‐onset or less‐severe disease phenotypes. Level of Evidence: 5 Laryngoscope, 131:E1941–E1949, 2021